Serum Symmetric Dimethylarginine as an Early Marker of Excretory Dysfunction in Canine Leishmaniosis (L. infantum) Induced Nephropathy - Esther Torrent; Marta Planellas; Laura Ordeix; Josep Pastor; Jaume Rodon; Laia Solano-Gallego (Veterinary Medicine International)
The aims of the study were to determine whether symmetric dimethylarginine (SDMA) was increased in dogs with leishmaniosis and to assess its relationship with creatinine concentration and urinary protein : creatinine ratio (UPC) to determine its utility as a marker of early excretory dysfunction. Fifty-three dogs with leishmaniosis classified according to the LeishVet clinical staging (stage I, n=5, stage II, n=30; stage III, n=12; stage IV, n=6) were selected and compared with 41 clinically healthy dogs. Thirty-nine dogs with leishmaniosis were also followed up for six months. SDMA concentrations on the day of diagnosis were significantly higher in dogs with leishmaniosis with respect to control dogs and in dogs from LeishVet stage IV when compared with the other stages. Increased UPC (>0.5), SDMA (>19 μg/dL), and creatinine concentrations (≥1.4 mg/dL) were found in 47.1%, 15.1%, and 9.4% of dogs with leishmaniosis, respectively. SDMA concentration was increased in 24% of proteinuric dogs, in 7% of nonproteinuric dogs, and in four of five dogs with increased creatinine. SDMA concentration ≥ 25 μg/dL was associated with clinical chronic kidney disease (CKD) after six months. Our results did not demonstrate advantages in using SDMA concentration as an early marker of CKD when compared to creatinine and UPC in canine leishmaniosis.